Luck versus Skill in the Cross‐Section of Mutual Fund Returns - FAMA, EUGENE F.; FRENCH, KENNETH R. (Journal of Finance, 2010)
ABSTRACT The aggregate portfolio of actively managed U.S. equity mutual funds is close to the market portfolio, but the high costs of active management show up intact as lower returns to investors. Bootstrap simulations suggest that few funds produce benchmark‐adjusted expected returns sufficient to cover their costs. If we add back the costs in fund expense ratios, there is evidence of inferior and superior performance (nonzero true α ) in the extreme tails of the cross‐section of mutual fund α estimates.